Bacterial contamination and antimicrobial susceptibility pattern of isolates from stethoscopes at a referral hospital in Tanzania (Tanzania Medical Journal, 2019)
BackgroundNosocomial infections pose a challenge to the medical field and are a global safety issue for both patients and health care providers. In developing countries, the magnitude of the problem remains underestimated and literature is very scarce. Some nosocomial infections spread via contaminated medical equipment such as stethoscopes. No data reported from Tanzania about the potential role of stethoscopes in spreading these infections.MethodsThis cross-sectional study was conducted to determine bacterial contamination and antimicrobial susceptibility of isolates at Kilimanjaro Christian Medical Centre (KCMC) from February to April 2014. One hundred medical doctors and medical students were randomly selected to participate in this study. Structured questionnaires were used to collect demographic data and behavioural information related to the cleaning and storage of stethoscopes. Participants’ stethoscopes were sampled with sterile moistened cotton swabs. Laboratory analysis was done following standard microbiological techniques in the Microbiology Unit. Data analysis was done using SPSS window version 16, and p-values of <0.05 were considered statistically significant.ResultsA total of forty-six of the stethoscopes were found to be contaminated. A total of 134 bacterial strains were isolated. Of 134 isolates, 70 were potentially pathogenic, including S. aureus, Klebsiella ssp, Proteus ssp, E. coli and P. aeruginosa. Eighteen percent of the S. aureus were methicillin-resistant.ConclusionWe found a significant amount of bacterial contamination of stethoscopes at our hospital, a significant percentage of which is Methicillin-Resistant Staphylococcus aureus (MRSA). Similar to other settings, in our setting in northern Tanzania, stethoscopes are important potential vehicles for nosocomial infections.Key words: Nosocomial infections, stethoscopes, MRSA, Tanzania.